2020
DOI: 10.1007/s41297-020-00112-6
|View full text |Cite
|
Sign up to set email alerts
|

The unfinished business of defining competences for 21st century curricula—a systematic research review

Abstract: Eighty-four articles are examined in this systematic research review, to provide a synthesis of the state of art with regard to educational research that focused on competence-based education (CBE) and curricula covering a period of 20 years from 1997 to 2017. Relying on PRISMA methodology and framed by discursive institutionalism, and curriculum and Didaktik traditions theoretically, the review was guided by two overarching research questions, focusing first on how much and what educational research on CBE ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
2
22
0
6
Order By: Relevance
“…The results of the comparison are in line with previous research on transnational competence frameworks (Tahirsylaj and Sundberg 2020;Voogt and Roblin 2012), and they show that organisations adopt different vocabularies, with some speaking of 'competency' and others of 'skills,' and that there are no standardised definitions for the sets of knowledge and skills induced by the twenty-first-century competence-based curricula. Instead, there are different competing ideas on what terms to use, what frameworks to relate to, and how to manage these terms and frameworks discursively within national curriculummaking.…”
Section: A Complex Context For National Curriculum-makingsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of the comparison are in line with previous research on transnational competence frameworks (Tahirsylaj and Sundberg 2020;Voogt and Roblin 2012), and they show that organisations adopt different vocabularies, with some speaking of 'competency' and others of 'skills,' and that there are no standardised definitions for the sets of knowledge and skills induced by the twenty-first-century competence-based curricula. Instead, there are different competing ideas on what terms to use, what frameworks to relate to, and how to manage these terms and frameworks discursively within national curriculummaking.…”
Section: A Complex Context For National Curriculum-makingsupporting
confidence: 84%
“…These definitions have much in common and all include general elements of collaboration, communication, ICT literacy, and social/cultural skills, often along with skills such as civic participation, creativity, critical thinking, and problem-solving (see also Voogt and Roblin 2012). A systematic research review on competence-based curricula in international literature (Tahirsylaj and Sundberg 2020) shows that one of the most quoted and influential definitions of competences comes from Franz E. Weinert, in which they are viewed as the 'cognitive skills and abilities individuals possess or can learn to solve particular problems, and the associated motivational, volitional and social readiness and abilities to solve problems successfully and responsibly in a variety of situations' (Weinert 2001, 27). This definition was also used in the influential OECD DeSeCo project, which accordingly defines competence as 'the ability to successfully meet complex demands in a particular context' (Rychen, Salganik, and McLaughlin 2003, 2).…”
Section: Transnational Competence Frameworkmentioning
confidence: 99%
“…Considering the chronology of competence-based education (CBE) since the 1990s, three key projects and developments stand out as critical to understanding the spread of CBE internationally. The first is the OECD's Definition and Selection of Key Competences (DeSeCo) in the second part of 1990s; second, the introduction of OECD's PISA in 2000; and third, the adoption of European Commission recommendations on key competences in 2006 (Tahirsylaj and Sundberg 2020). Despite a number of definitions available, competences have been defined as a combination of knowledge, skills and attitudes appropriate to the context, and key competences, specifically, are those that all individuals need for personal fulfilment and development, active citizenship, social inclusion and employment (OJEU 2006).…”
Section: Civic Competences In Kosovo Curriculum Framework and Ec Docmentioning
confidence: 99%
“…The study of studies and publications devoted to the problems of defining the competencies of graduates of higher professional education institutions and their compliance with the requirements of employers allowed to form the main conclusion about the incompleteness of the discussion regarding definitions, terminologies, meanings, structural elements and other categories of the scientific problem of filling the competencies of a graduate of higher education institutions with content. In this connection, the study [3], where the authors have done a huge scientific work, which is a systematic review where 84 scientific articles are considered, turned out to be indicative of interest. The review aimed to summarize the current level of research focused on education and curricula, touching on the concept of competencies and covering a period of 20 yearsfrom 1997 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this review, the authors suggested that there are two different labels for "competencies" in education [2]. Namely: from the theoretical point of view, competence is conceived as a cognitive structure that promotes a certain behavior; from the operational point of view, competencies, the authors suggest, cover a wide range of higher-order skills and behaviors, representing the ability to deal with complex, unpredictable situations; this operational definition includes knowledge, skills and strategic thinking, and assumes conscious and intentional decision-making [3]. Also, competence is defined as the integration of knowledge, skills and attitudes that allow a person to perform a certain task in vaguely defined and unique environments [4].…”
Section: Introductionmentioning
confidence: 99%